PENGARUH STRES KERJA DAN KONFLIK KERJA TERHADAP SEMANGAT KERJA PT. PEMBANGKIT JAWA BALI SERVICES KECAMATAN MERAPI TIMUR KABUPATEN LAHAT - Saparudin . (Fakultas Ekonomi Universitas Tridinanti Palembang, 2017)
This study aims to determine the effect of Job Stress on the Spirit of Work PT. Java Bali Services Plant East Merapi District Lahat District, the influence of Work Conflicts on the Spirit of Work PT. Java Bali Services Plant East Merapi District Lahat District, and Work Stress And Work Conflicts Kheaterhadap Spirit Work PT. Java Bali Services Plant East Merapi District Lahat District.The sample in this study amounted to 60 respondents who distributed to employees of PT. Java Bali Services Plant East Merapi District Lahat District. Data analysis method used is quantitative analysis by using validity test, reliability test, classical assumption test, multiple linear regression analysis and average difference test.Work Stress results have a positive and significant impact on employee morale. It can be seen from t count> t table (13,067> 2,002). Work Conflicts have a positive and significant impact on employee morale. This can be seen from the value of t arithmetic> t table (3.609> 2,002). And Work Stress And Conflict Work simultaneously have a positive and significant impact on employee morale. It can be seen from the value of F arithmetic> F table (111,086> 2,20) and significance value <tality level (α) 0,05 (0,000 <0,05). Keywords: Work Conflicts, Job Stress, and Morale